2021
DOI: 10.52142/omujecm.38.si.dent.13
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of artificial intelligence in orthodontics

Abstract: The clinical use of artificial intelligence technology in orthodontics has increased significantly in recent years. Artificial intelligence can be utilized in almost every part of orthodontic workflow. It is an important decision making aid as well as a tool for building more efficient treatment mechanics. The use of artificial intelligence reduces costs, speeds up the diagnosis and treatment process and reduces or even eliminates the need for manpower. This review article evaluates the current literature on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Overall, the AI algorithm architecture (CNN, ANN) showed promising results in cephalometric landmark detection and analysis compared with human subjects, as shown in Table 1 . Moreover, 19 articles [ 5 , 6 , 8 , 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were excluded from this review, as shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the AI algorithm architecture (CNN, ANN) showed promising results in cephalometric landmark detection and analysis compared with human subjects, as shown in Table 1 . Moreover, 19 articles [ 5 , 6 , 8 , 9 , 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] were excluded from this review, as shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, dental monitoring software that uses AI has proven effective during the treatment phase to track progress, as well as during the retention phase to detect relapse and assess the stability of treatment outcomes, with the benefit of assessing the compliance of patients even without regular in-office visits [41]. After all, the goal of modern technologies is to make dental care high-quality, smooth, time-efficient and cost-effective, with improved treatment planning as well as risk management, and AI certainly adds up to that [46,74,75].…”
Section: Artificial Intelligence Tools and Datasetsmentioning
confidence: 99%
“… 15 , 16 Machine learning can be used for several important functions in Orthodontics: descriptive, predictive, and prescriptive. 17 , 18 Descriptive functions in Orthodontics can be linked to the formulation of a diagnosis when the different parameters (inputs) are considered 19 . Predictive, as its name implies, is meant to predict the most accurate outcome of a potential treatment - in Orthodontics, it could be the decision to extract or not extract.…”
Section: Architecture Of the Multilayer Perceptron And Of A Simple Ne...mentioning
confidence: 99%